2006
DOI: 10.1007/s10531-006-9121-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of soil-inhabiting fungi

Abstract: This survey is concerned only with filamentous fungi living in the soil layer. The observed diversity of soil fungi largely depends on the method used and the numbers of isolates obtained. Particle-plating usually yields higher numbers of taxa than dilution plating. The Centraalbureau voor Schimmelcultures (CBS) preserves a great diversity of soil fungi. The CBS database contained 2,210 species of soil fungi in 2001, an estimated 70% of the known species available in culture. Thus, the current estimate for des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 12 publications
1
38
1
4
Order By: Relevance
“…Hawksworth and Rossman estimated there may be as many as 1 million different fungal species, yet only about 100,000 have been described (Hawksworth and Rosmann 1987, Vandenkoornhuyse et al 2002, Gams 2007. It remains to be seen which fraction of the unknown fungi can be isolated and characterized in the laboratory but even now we can expect that they will contribute novel and unique volatile sesquiterpenes.…”
Section: Discussionmentioning
confidence: 99%
“…Hawksworth and Rossman estimated there may be as many as 1 million different fungal species, yet only about 100,000 have been described (Hawksworth and Rosmann 1987, Vandenkoornhuyse et al 2002, Gams 2007. It remains to be seen which fraction of the unknown fungi can be isolated and characterized in the laboratory but even now we can expect that they will contribute novel and unique volatile sesquiterpenes.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of soil-and rhizosphere-inhabiting fungi is much higher than previously thought (Vandenkoornhuyse et al, 2002;Gams, 2007). Molecular tools were developed to analyse the structure of terrestrial fungal communities (Kowalchuk, 1999;Vainio and Hantula, 2000;Anderson and Cairney, 2004;Berg et al, 2005), but little is known about their diversity, biogeography and ecology, especially in native ecosystems.…”
mentioning
confidence: 99%
“…Soil texture, organic matter content, carbonate content, pH and cation exchange capacity (CEC) can all significantly affect the diversity and abundance of soil fungi, which is why the aim of this study was to determine the influence of soil properties on the biodiversity of fungi. It is likely that we currently know at least 30% of the total diversity of soil fungi, and the number of species of soil fungi is expected to be considerably higher than the 3300 species currently known (Gams, 2007). This research contributes to a better knowledge of the biodiversity and the mycobiota present in soil samples of different types and usage.…”
Section: Introductionmentioning
confidence: 93%
“…This result can also be compared to the results obtained by authors from all over the world where those species were also reported as common species in soybean soil rhizosphere in India (Maisuria, Patel, 2009), soil and litter samples of Forest Reserve in Trat Province in Thailand (Puangsombat et al, 2010) and litter samples from different forest types in China (Song et al, 2004). It is known that even in tropical forests, many taxa are similar to taxa found in temperate latitudes, and the numbers of species for a particular tropical soil are normally the same or even lower than those observed for soils in temperate regions (Gams, 2007). Fungi from the genera Penicillium, Aspergillus, Cladosporium, Fusarium, Rhizopus, Mucor, Phoma and Verticillium were even found in reservoirs of lakes and rivers in Serbia (Ranković, 2005).…”
Section: Analyses Of Physical and Chemical Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation